The Role of Creative Drama in Improving the Creativity of 4-6 Years Old Children - Momeni, Sedighe; Khaki, Mohammadreza; Amini, Rahmat (Journal of History Culture and Art Research, 2017)
The present study examines the influence of creative drama on the creativity of 4 to 6 years old children. Accordingly, using a multi-stage cluster sampling, 52 children (21 girls and 31 boys), of district of Ahwaz city, were chosen and then randomly divided into two groups of experimental (33 people) and control (19 people). The researched was directly involved in intervention as regarded the experimental group. The intervention group participated in creative drama activities for two months (15 sessions). The creativity level of the children in these two groups, before and after the intervention, was measured using the creativity test of Jean-Louis Cellier? This test includes verbal creativity, completing and interpreting the pictures that are determinative of creativity components, fluidity, extension, flexibility and originality. The data and the results were analyzed based on descriptive statistical and inferential methods such as frequency, mean, standard deviation and non-parametric rank (Kruskal-Wallis, Wilcoxon and the Spearman correlation). The results indicated that the creative drama significantly increased the creativity of children at the ages of 4 to 6.